2015
DOI: 10.2807/1560-7917.es.2015.20.44.30053
|View full text |Cite|
|
Sign up to set email alerts
|

Development and deployment of a rapid recombinase polymerase amplification Ebola virus detection assay in Guinea in 2015

Abstract: In the absence of a vaccine or specific treatments for Ebola virus disease (EVD), early identification of cases is crucial for the control of EVD epidemics. We evaluated a new extraction kit (SpeedXtract (SE), Qiagen) on sera and swabs in combination with an improved diagnostic reverse transcription recombinase polymerase amplification assay for the detection of Ebola virus (EBOV-RT-RPA). The performance of combined extraction and detection was best for swabs. Sensitivity and specificity of the combined SE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 18 publications
(17 reference statements)
0
97
0
Order By: Relevance
“…Organizations such as the Centers for Disease Control and Prevention, USA, the National Institutes for Health, USA, the World Health Organization and the European Committee for Standardization should revise international recommendations accordingly. Technical advances arising from the successful deployment of mobile BSL-3 laboratories in the West African outbreak of Ebola disease (Chen et al, 2015;Faye et al, 2015;Inglis, 2015;Wölfel et al, 2015) should be exploited to derive cost-effective improvements to diagnostic laboratories in the CCHF endemic countries. In particular, the use of flexible-walled or hard plastic glove boxes for extraction of nucleic acids and inactivation of sera would greatly improve laboratory safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizations such as the Centers for Disease Control and Prevention, USA, the National Institutes for Health, USA, the World Health Organization and the European Committee for Standardization should revise international recommendations accordingly. Technical advances arising from the successful deployment of mobile BSL-3 laboratories in the West African outbreak of Ebola disease (Chen et al, 2015;Faye et al, 2015;Inglis, 2015;Wölfel et al, 2015) should be exploited to derive cost-effective improvements to diagnostic laboratories in the CCHF endemic countries. In particular, the use of flexible-walled or hard plastic glove boxes for extraction of nucleic acids and inactivation of sera would greatly improve laboratory safety.…”
Section: Discussionmentioning
confidence: 99%
“…Of 11 laboratories performing virus isolation and propagation, six did so in BSL-4 facilities and five in lowergrade facilities (Fernandez-Garcia et al, 2012). Enquiries made for purposes of the present review revealed that in Slovenia, Turkey and Senegal, CCHFV diagnostic samples were handled at BSL-2 for years before a BSL-3 laboratory was finally available for research.…”
Section: Biosafety Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, all of the deceased in districts of Conakry most recently affected by the Ebola virus outbreak had to be tested. The field deployment of a mobile suitcase laboratory using RPA which provided results in 30-40 minutes helped to improve burial management and community engagement in the Matoto district in Conakry [30].…”
Section: The 2014 Ebola Virus Outbreakmentioning
confidence: 99%
“…In this context, the IPD laboratory and collaborators adapted and optimised a rapid test based on isothermal reverse transcription recombinase polymerase amplification (RT-RPA) for the detection of Ebola virus [11,12]. A mobile laboratory consisting of a mobile glove box and a Diagnostics-in-Suitcase (DiaS) powered by a battery and solar panel was used.…”
Section: Development Of Rapid Testmentioning
confidence: 99%